UPAYA PEMURIDAN BAGI MAHASISWA MELALUI METODE KAMBIUM - Purba, Asmat (UPPM Politeknik TEDC Bandung, 2023)
Discipleship is the responsbility of Christian Religious Education lecturers. Lecturers who teach religious education are also disciples of Christ who carry out discipleship, taking an important role in confirming, nurturing and reaching averyone to become disciples of Christ. Studentsas an integral part of the church and nation are one of the targets of discipleship that should be considered because they are the baton holders as well as assets for the church. Discipleship for students is important so that their faith is well maintained and not carried away by progress that has the potential to trigger an attitude of axtravagance and worldly life. The CAMBIUM method can be an option in getting students throught discipleship. This paper aims to describe discipleship efforts for students through the CAMBIUM discipleship method. The research was carried out through a literature study which through the CAMBIUM discipleship method was significantly applied to students where the teaching model was carried out at three levels namely rooted, growing and bearing fruit in Christ.